Oh, the treasured memories at the reunions - Abd Razak, Dzulkifli (2008)
FORTY years seems a very long time. But, when gathering for a reunion, 40 years seem just like yesterday as experiences and faces neatly fall into place. It's much like a jigsaw puzzle meant for children. The pictures are vivid and large, the colours fresh and appealing. Most of all, it is fun as everything comes alive. At times, it is like reliving everything all over again, especially when it exudes happiness, in contrast to the predictions of gloom and doom ahead. I discovered this twice last week when my alma mater celebrated its 40th anniversary. Both occasions were equally grand and captivating as though we were in a timecapsule, flashing from point to point, just quick enough to sample the moments.